Estimated standard values of aerobic capacity according to sex and age in a Japanese population: A scoping review. - Hiroshi Akiyama; Daiki Watanabe; Motohiko Miyachi (PLoS ONE)
Aerobic capacity is a fitness measure reflecting the ability to sustain whole-body physical activity as fast and long as possible. Identifying the distribution of aerobic capacity in a population may help estimate their health status. This study aimed to estimate standard values of aerobic capacity (peak oxygen uptake [Formula: see text] and anaerobic threshold [AT]/kg) for the Japanese population stratified by sex and age using a meta-analysis. Moreover, the comparison of the estimated standard values of the Japanese with those of other populations was performed as a supplementary analysis. We systematically searched original articles on aerobic capacity in the Japanese population using PubMed, Ichushi-Web, and Google Scholar. We meta-analysed [Formula: see text] (total: 78,714, men: 54,614, women: 24,100) and AT (total: 4,042, men: 1,961, women: 2,081) data of healthy Japanese from 21 articles by sex and age. We also searched, collected and meta-analysed data from other populations. Means and 95% confidence intervals were calculated. The estimated standard values of [Formula: see text] (mL/kg/min) for Japanese men and women aged 4-9, 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, and 70-79 years were 47.6, 51.2, 43.2, 37.2, 34.5, 31.7, 28.6, and 26.3, and 42.0, 43.2, 33.6, 30.6, 27.4, 25.6, 23.4, and 23.1, respectively. The AT/kg (mL/kg/min) for Japanese men and women aged 20-29, 30-39, 40-49, 50-59, 60-69, and 70-79 years were 21.1, 18.3, 16.8, 15.9, 15.8, and 15.2, and 17.4, 17.0, 15.7, 15.0, 14.5, and 14.2, respectively. Herein, we presented the estimated standard values of aerobic capacity according to sex and age in a Japanese population. In conclusion, aerobic capacity declines with ageing after 20-29 years of age. Additionally, aerobic capacity is lower in the Japanese population than in other populations across a wide range of age groups. Standard value estimation by meta-analysis can be conducted in any country or region and for public health purposes.